The effect of particle size on the dispersion and wear protection ability of MoS2 particles in polyalphaolefin and trimethylolpropane ester. (August 2018) - Gulzar, M; Mahmood, Khalid; Zahid, Rehan; Alabdulkarem, Abdullah; Masjuki, HH; Kalam, MA; Varman, M; Zulkifli, NWM; Ahmad, Pervaiz; Malik, MSS
The effect of particle size and surfactant on dispersion stability and wear protection ability was experimentally evaluated for polyalphaolefin (PAO 10) and bio-based base oil (palm trimethylolpropane ester) added with molybdenum disulfide (MoS2 ) particles. Nanolubricants were developed by adding 1 wt% of MoS2 particles that varied in size. In addition to the variation in particle size, an anionic surfactant was also used to analyze its interaction with both types of nanoparticles for stable suspensions and for the related effects on the antiwear characteristics. The wear protection characteristics of the formulations were evaluated by four-ball extreme pressure tests and piston ring on cylinder sliding wear tests. The wear surfaces were analyzed by scanning electron microscopy along with an energy-dispersive X-ray and an atomic force microscopy. The MoS2 nanoparticles with a nominal size of 20 nm exhibited a better load-carrying capacity, while better sliding wear protection was provided by nanoparticles with a nominal size of 50 nm.